2020
DOI: 10.1140/epjqt/s40507-020-00087-3
|View full text |Cite
|
Sign up to set email alerts
|

OPM magnetorelaxometry in the presence of a DC bias field

Abstract: Spatial quantitative information about magnetic nanoparticle (MNP) distributions is a prerequisite for biomedical applications like magnetic hyperthermia and magnetic drug targeting. This information can be gathered by means of magnetorelaxometry (MRX) imaging, where the relaxation of previously aligned MNP’s magnetic moments is measured by sensitive magnetometers and an inverse problem is solved. To remove or minimize the magnetic shielding in which MRX imaging is carried out today, the knowledge of the influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Turning our attention again to nonzero fields, Jaufenthaler et al 87 showed how the relaxation time was already affected by small DC fields (< 100 µT) and their applied direction 87 . Similarly, the measured phase lag in MSI is also related to these relaxation time constants and could provide information on changes in particle dynamics and interactions for the case of small AMFs.…”
Section: A Exploiting Complex Magnetic Particle Dynamicsmentioning
confidence: 99%
“…Turning our attention again to nonzero fields, Jaufenthaler et al 87 showed how the relaxation time was already affected by small DC fields (< 100 µT) and their applied direction 87 . Similarly, the measured phase lag in MSI is also related to these relaxation time constants and could provide information on changes in particle dynamics and interactions for the case of small AMFs.…”
Section: A Exploiting Complex Magnetic Particle Dynamicsmentioning
confidence: 99%
“…Today, there are many different OPM configurations, covering a broad range of applications 36,[45][46][47][48] . Comparisons have been made with SQUID systems [49][50][51] and the magnetometers have also found their way into applications such as MNP detection, characterization and imaging [52][53][54][55][56][57] .…”
Section: Opm Tabletop Setup For Thermal Noise Magnetometrymentioning
confidence: 99%
“…36,[45][46][47][48] Comparisons have been made with SQUID systems [49][50][51] and the magnetometers have also found their way into applications such as MNP detection, characterization, and imaging. [52][53][54][55][56][57] The developed tabletop setup (Fig. 3a) consists of two Gen-2 QuSpin zero-eld magnetometers (QZFMs) (QuSpin Inc., CO, USA) 58 that are operated in single-axis mode.…”
Section: Experimental Setupsmentioning
confidence: 99%
“…The remanent magnetization can be exploited in MRX imaging [ 60 ]. In this respect it is worth noting that in unshielded experiments, the Earth’s field (or any other bias field) contributes non-neglectably to the remanent magnetization and to the relaxation behavior of the MNP [ 64 , 65 ].…”
Section: Conclusion and Outlookmentioning
confidence: 99%